1997
DOI: 10.1002/(sici)1096-9861(19971208)389:1<65::aid-cne5>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl-D-aspartate receptor 1 mRNA distribution in the central nervous system of the weakly electric fishApteronotus leptorhynchus

Abstract: We have isolated a partial cDNA for the N-methyl-D-aspartate (NMDA) receptor 1 (NMDAR1) subunit from an Apteronotus leptorhynchus brain cDNA library. The A. leptorhynchus cDNA fragment, which corresponds to nucleotides 135-903 within the 5' region of the rat NR1 mRNA, encodes 252 amino acids that are >80% identical to the homologous segments of the rat, human, and duck NR1 proteins. RNAse protection assays revealed that the A. leptorhynchus NR1 mRNA was highly enriched in the forebrain and hypothalamus, with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 72 publications
5
46
0
Order By: Relevance
“…The primers used were as follows: forward, 5Ј-ATCTTYGGIATGTTYGGIATIGT-3Ј, and reverse, 5Ј-TATAGATIAGCCAIGTYTCY-3Ј, where Y is CϩT and I is inosine. PCR was performed on brain cDNA from A. leptorhynchus (Bottai et al, 1997). The product of the degenerate reverse transcription-PCR (900 bp) was cloned into the pGEM-T vector (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…The primers used were as follows: forward, 5Ј-ATCTTYGGIATGTTYGGIATIGT-3Ј, and reverse, 5Ј-TATAGATIAGCCAIGTYTCY-3Ј, where Y is CϩT and I is inosine. PCR was performed on brain cDNA from A. leptorhynchus (Bottai et al, 1997). The product of the degenerate reverse transcription-PCR (900 bp) was cloned into the pGEM-T vector (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…Especially prominent coexpression of NMDA receptors (NR1 subunit) and CaMKII is evident in ELL pyramidal cells and in neurons of the dorsal forebrain (Bottai et al 1997;Maler and Hincke 1999); preliminary studies (in situ hybridization) have demonstrated that the AptNR2B subunit is also abundant at both sites (R. Dunn, unpublished observations.). It will therefore be interesting to determine whether the activity-dependent association of AptNR2B and CaMKII is part of the molecular basis of adaptive sensory filtering in ELL (Bastian 1999).…”
Section: Evolutionary Conservation Of Regulatory Sites On the Cterminmentioning
confidence: 97%
“…Recent studies have demonstrated that the dorsolateral forebrain of teleost fish is essential for spatial memory (Rodriguez et al 2002) and have suggested that this region is similar to mammalian hippocampus. In Apteronotus, this brain region has very high levels of NR1 (Bottai et al 1997), AptNR2B (R. Dunn and L. Maler, unpublished observations), and CaMKII (Bottai et al 1997). Both spatial memory and synaptic plasticity (long-term potentiation) in the hippocampus require intact interactions between NR2B and CaMKII (Malenka and Nicoll 1999); given the relative simplicity of teleost forebrain, our results suggest that this may prove to be a useful preparation for investigating the cellular basis of spatial memory.…”
Section: Evolutionary Conservation Of Regulatory Sites On the Cterminmentioning
confidence: 99%
See 2 more Smart Citations